Causal associations between gut microbiota and regional cortical structure: a Mendelian randomization study - Zhou, Maochao; Chen, Song; Chen, Yan; Wang, Chunhua; Chen, Chunmei (Frontiers in Neuroscience, 2023)
Introduction: Observational studies have reported associations between gut microbiota composition and central nervous system diseases. However, the potential causal relationships and underlying mechanisms remain unclear. Here, we applied Mendelian randomization (MR) to investigate the causal effects of gut microbiota on cortical surface area (SA) and thickness (TH) in the brain. Methods: We used genome-wide association study summary statistics of gut microbiota abundance in 18,340 individuals from the MiBioGen Consortium to identify genetic instruments for 196 gut microbial taxa. We then analyzed data from 56,761 individuals from the ENIGMA Consortium to examine associations of genetically predicted gut microbiota with alterations in cortical SA and TH globally and across 34 functional brain regions. Inverse-variance weighted analysis was used as the primary MR method, with MR Egger regression, MR-PRESSO, Cochran’s Q test, and leave-one-out analysis to assess heterogeneity and pleiotropy. Results: At the functional region level, genetically predicted higher abundance of class Mollicutes was associated with greater SA of the medial orbitofrontal cortex (β = 8.39 mm2, 95% CI: 3.08-13.70 mm2, P = 0.002), as was higher abundance of phylum Tenericutes (β = 8.39 mm2, 95% CI: 3.08-13.70 mm2, P = 0.002). Additionally, higher abundance of phylum Tenericutes was associated with greater SA of the lateral orbitofrontal cortex (β =10.51 mm2, 95% CI: 3.24-17.79 mm2, P = 0.0046). No evidence of heterogeneity or pleiotropy was detected. Conclusion: Specific gut microbiota may causally influence cortical structure in brain regions involved in neuropsychiatric disorders. The findings provide evidence for a gut-brain axis influencing cortical development, particularly in the orbitofrontal cortex during adolescence.